ANAK SEBAGAI FUTURE MARKET: STUDl AUTOBIOGRAPHICAL MEMORY - Eristia Lidia Paramita; John J.O.I. Ihalauw (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2010)
Kids as future market are one of the potential markets. Besides, many factors may influence in the process to be the future market, such as, children’s internal and external environments. This study used one of the psychological concepts, autobiographical memory that focuses on the unforgettable memory in children in their late period (12-14 years). The aims of the study are to describe the use of autobiographical memory in children’s late period and contribute to the understanding of brand loyalty and brand switching, especially in toothpaste product. The research questions are (1) the condition of toothpaste usage in children’s late period; (2) the brands commonly used by the children’s late period; (3) the children’s late period autobiographical memory when they use those brands (4) the willingness to keep on using those brands; and (5) the tendencies to switch brands. Purposive sampling method is used. The sample size is 218 children age 12-14 years old in 2 private and state junior high school. The study used descriptive statistic analysis. The analysis shows that the autobiographical memory is one of the factors to make the children loyal to the brand. However, they also could switch the brand. In their early age, children age 12-14 years old do not have the freedom to purchase products, because their reference groups still have influence in their life. The study shows 71.1% of the sample commonly use Pepsodent, 15% Close Up, Ciptadent, Enzim and Antiplaque are in the third, fourth and fifth place. The product feature, product image, and product accessibility have impacts on the autobiographical memory due to the consumption of the toothpaste. Pepsodent is the most unforgettable toothpaste brand (70.64%), followed by Close Up (31.1%), Ciptadent (21.1%), and Formula (19.27%). The children’s late period are in grey area between loyal to the brand and switch to another brand.The results show several important concepts that are further used to formulate propositions and a model.